Is Interview Length Associated With Blood Test Participation? Evidence From Three Population-Based HIV Impact Assessment Surveys Conducted From 2016 to 2017. (1st August 2021) - Bray, Rachel; Palma, Anton M.; Philip, Neena M.; Brown, Kristin; Levin, Bruce; Thompson, John L. P. (Seamus); Ginindza, Choice; Mulenga, Lloyd B.
Abstract : Background: High response rates in surveys are critical to ensuring that findings are unbiased and representative of the target population. Questionnaire length affects response rates, with long interviews associated with partially complete surveys, higher item nonresponse ("don't know" and "refuse" responses), and willingness to participate in future surveys. Our aim is to determine the impact of questionnaire length on blood test participation in population-based HIV surveys. Methods: Data are from population-based HIV impact assessments conducted in Zambia, Eswatini, and Lesotho in 2016–2017. The population-based HIV impact assessments consist of an interview followed by a blood draw. Consent for blood draw was obtained before the interview in Eswatini and after the interview in Zambia and Lesotho. Interview length was measured by the survey tablet as the time to complete the survey (interview duration) and the number of questions answered by the participant (questionnaire length). We assessed the effects of questionnaire length and interview duration on blood test participation using logistic regression. Results: Across all 3 surveys, the median interview duration was 16 minutes and the median number of questions was 77. In adjusted analyses, there was a negative impact of interview duration on blood draw consent for individuals with unknown status in Lesotho and a positive relationship between questionnaire length and blood draw consent in Zambia for those with HIV-negative and unknown status. Conclusion: Although interview length is an important consideration to reduce respondent burden, a longer questionnaire does not necessarily result in lower consent rates for blood testing. Abstract : Supplemental Digital Content is Available in the Text.